Negative pole piece, preparation method of negative pole piece and battery

By adopting a multi-layer structure and groove design in the negative electrode sheet of lithium-ion battery, the application efficiency of silicon-based negative electrode materials is improved, and the problems of low efficiency and energy density of the battery are solved for the first time, achieving higher battery performance and Lower bad rate.

CN119208536AActive Publication Date: 2024-12-27HONOR DEVICE CO LTD

Patent Information

Application Number
CN202411589450.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-27
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The application of silicon-based anode materials in lithium-ion batteries is limited, mainly because their morphology and structure are damaged during the deintercalation of lithium, resulting in low efficiency of the battery for the first time, and the quality of silicon-based anode materials account for a low proportion.

Method used

A negative electrode sheet structure is adopted, including a first active layer, a second active layer and a third active layer stacked in sequence on the current collector, the first and third active layers contain carbon materials, the second active layer contains silicon materials, The silicon material mass percentage of the two active layer is greater than 10%, and grooves are provided on the third active layer to increase the electrolyte contact area and reduce tortuosity.

Benefits of technology

The first-time Coulomb efficiency, energy density and battery capacity of the battery are improved, and the defect rate of Hi-Pot test is reduced. By enhancing the contact between the active layer and the electrolyte and reducing material shedding, the charging and discharging performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208536A_ABST
    Figure CN119208536A_ABST
Patent Text Reader

Abstract

The invention discloses a negative pole piece, a preparation method of the negative pole piece and a battery. The negative pole piece comprises a current collector and an active layer, the active layer is arranged on the current collector, the active layer comprises a first active layer, a second active layer and a third active layer which are sequentially arranged on the current collector in a stacked mode, the first active layer is closer to the current collector than the second active layer, and a groove is formed in the side, away from the second active layer, of the third active layer. The first active layer and the third active layer comprise a carbon material, the second active layer comprises a silicon material, and the mass percentage of the silicon material in the second active layer is greater than 10%. According to the negative pole piece provided by the invention, the first coulombic efficiency, the battery capacity and the energy density of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a negative electrode sheet, a method for preparing a negative electrode sheet, and a battery. Background Art

[0002] Silicon-based negative electrode materials have high gram capacity, high volumetric capacity, and suitable lithium insertion potential, which can improve the energy density of lithium-ion batteries. Therefore, silicon-based negative electrode materials are a very promising negative electrode material for lithium-ion batteries. However, in the continuous process of lithium insertion and extraction, the morphology and structure of silicon will be destroyed, resulting in a low initial coulombic efficiency of the battery. In addition, the mass proportion of silicon-based negative electrode materials in related technologies is relatively low, which limits the application of silicon-based negative electrode materials in lithium-ion batteries. Summary of the invention

[0003] In order to solve the above technical problems, the present application provides a negative electrode plate, a method for preparing a negative electrode plate and a battery, which can improve the battery's first coulombic efficiency, battery capacity and energy density.

[0004] A first aspect of the present application provides a negative electrode plate, the negative electrode plate comprising a current collector and an active layer, the active layer being arranged on the current collector, the active layer comprising a first active layer, a second active layer and a third active layer stacked in sequence on the current collector, the first active layer being closer to the current collector than the second active layer, and a groove being arranged on a side of the third active layer away from the second active layer, wherein the first active layer and the third active layer comprise carbon material, the second active layer comprises silicon material, and the mass percentage of the silicon material in the second active layer is greater than 10%.

[0005] The negative electrode plate provided by the present application has the first active layer, the second active layer and the third active layer stacked in sequence on the current collector. Since the first active layer including carbon material is close to the current collector, the bonding force between the second active layer and the first active layer is greater than the bonding force between the second active layer and the current collector, thereby preventing the second active layer including silicon material from falling off from the current collector due to expansion, thereby improving the first coulomb efficiency, energy density and battery capacity of the battery. Moreover, since the mass percentage of silicon material in the second active layer is greater than 10%, the active layer has a higher silicon content, further improving the energy density and battery capacity. In addition, the groove can increase the contact area between the active layer and the electrolyte, thereby improving the infiltration effect of the electrolyte, and can also reduce the tortuosity, increase the battery charge and discharge rate, and increase the battery charge and discharge rate. Specifically, since the groove can be used as a transmission path for ions such as lithium ions, lithium ions can reach the interior of the active layer more directly and quickly, thereby reducing the tortuosity.

[0006] In a possible implementation, the third active layer further includes a first polymer, the first polymer is formed by in-situ polymerization of a first precursor in the first active layer, and the first polymer is mixed with the carbon material and distributed in the third active layer.

[0007] When the grooves are opened, after the materials of the third active layer located in the grooved area, especially the binder, escape, the bonding strength between the material particles of the remaining materials will be weakened, and the first precursor in the grooved area is polymerized to generate the first polymer to form a cross-linked network, which can bond the material particles of the remaining materials of the third active layer in the grooved area, thereby improving the bonding strength between the material particles of the third active layer at the groove position, thereby avoiding the material particles at this position from falling off, thereby reducing the carbon material escape, and further reducing the Hi-Pot test failure rate, and avoiding the falling off of carbon material particles can improve the first coulomb efficiency and energy density. In addition, the first precursor located at other positions is polymerized to generate the first polymer, which can enhance the bonding strength between the material particles of the third active layer at the corresponding position.

[0008] In a possible implementation manner, the structure of the first precursor includes an aromatic ring and a double bond.

[0009] The structure of the first precursor includes a double bond so that the first precursor can undergo a polymerization reaction. The structure of the first precursor includes an aromatic ring, that is, the first polymer generated by in-situ polymerization also includes an aromatic ring, so that the polarity of the first polymer is relatively weak. Due to the principle of like favors like, the first polymer with relatively weak polarity has good affinity with the non-polar carbon material in the third active layer, so that the first polymer and the carbon material in the third active layer have good compatibility, the first polymer and the carbon material have a large adhesion force, and a relatively stable structure can be formed.

[0010] In a possible implementation, the first precursor includes at least one of allylbenzene, allylbenzyl ether, 2-allylphenyl allyl ether and 2-allylbenzaldehyde.

[0011] The polymerization reaction of these precursors has high reaction efficiency, and the generated first polymer can better bond the materials of the third active layer together. In addition, these precursors have high chemical stability and low cost.

[0012] In a possible implementation manner, the mass percentage of the first polymer in the third active layer is 3%-5%.

[0013] The mass percentage of the first polymer within this range can not only achieve a good bonding effect, thereby reducing the Hi-Pot test failure rate, but also increase the first coulombic efficiency, battery capacity and energy density.

[0014] In a possible implementation, the second active layer further includes a second polymer, the second polymer is formed by in-situ polymerization of a second precursor in the second active layer, and the second polymer is mixed with the silicon material and distributed in the second active layer.

[0015] During the grooving, after the material of the second active layer located in the grooving area, especially the binder, escapes, the bonding strength between the material particles of the remaining material will be weakened, and the second precursor in the grooving area is polymerized to generate the second polymer to form a cross-linked network, which can bond the material particles of the remaining material of the second active layer in the grooving area, thereby improving the bonding strength between the material particles of the second active layer at the groove position, thereby reducing the escape of silicon material, and further reducing the Hi-Pot test failure rate, and avoiding the shedding of silicon material particles can improve the first coulomb efficiency and energy density. In addition, the second precursor located at other positions is polymerized to generate the second polymer, which can enhance the bonding strength between the material particles of the second active layer at the corresponding position. The second polymer can also inhibit the expansion of silicon material particles in the second active layer.

[0016] The structure of the second precursor includes a double bond, so that the second precursor can undergo a polymerization reaction. The structure of the second precursor includes an ether oxygen bond, which has a strong polarity and can produce a strong interaction with ions such as lithium ions, such as adsorption and coordination, so as to improve the ion transport performance of the second active layer, thereby improving the kinetic performance of the battery.

[0017] In a possible implementation, the second precursor includes at least one of polyethylene glycol diacrylate, polyethylene glycol methyl ether acrylate, and polyethylene glycol methyl ether methacrylate.

[0018] The polymerization reaction of these precursors has high reaction efficiency, and the generated second polymer can better bond the materials of the second active layer together. In addition, these precursors have high chemical stability and low cost.

[0019] In a possible implementation, the weight average molecular weight of the second precursor is 400-20000, so that the polymerization efficiency of the second precursor is high and the second precursor is not easy to agglomerate in the slurry.

[0020] In a possible implementation, the mass percentage of the second polymer in the second active layer is 3%-5%, which not only has a good bonding effect, and thus a low Hi-Pot test failure rate, but also has high first coulomb efficiency, battery capacity, and energy density.

[0021] In one possible implementation, the negative electrode plate also includes a polymer layer, which is arranged between the third active layer and the second active layer, and the polymer layer includes a third polymer. The structure of the third polymer includes a first group and a second group, the first group includes at least one of a carboxyl group, a carboxylate group, an amide group, a hydroxyl group, a cyano group and an ester group, and the second group includes an aromatic group.

[0022] The first group in the third polymer has strong polarity, and forms hydrogen bonds or dipole-dipole interactions with the surface groups of the silicon material in the second active layer, which can enhance the bonding performance between the polymer layer and the second active layer. The second group in the third polymer is a non-polar group, and the second group can form a π…π interaction with the carbon material in the third active layer, which can enhance the bonding performance between the polymer layer and the third active layer. Thus, the polymer layer can play a bonding role, and the polymer layer is arranged between the second active layer and the third active layer, which can increase the bonding force between the second active layer and the third active layer. When the third active layer is grooved, the second active layer and the third active layer can be prevented from being partially separated under the action of external energy. For example, when the third active layer is grooved using a laser, the second active layer and the third active layer can be prevented from being partially separated under the action of light and heat, thereby avoiding the material particles of the third active layer and the material particles of the second active layer from falling off as much as possible, thereby further reducing the Hi-Pot test failure rate and improving the first coulomb efficiency.

[0023] In a possible implementation, the third polymer has a structure shown in Formula I, Formula I, wherein R1 is the first group, R2 is the second group, R3 and R4 include at least one of carboxyl, hydroxyl, amino and hydrogen, n and m are integers between 10 and 10000, and the ratio of n to m is 0.1 to 10.

[0024] If n and m are less than 10, the molecular weight of the third polymer will be low, which may cause the polymer layer to have strong fluidity during processing and be difficult to form a stable coating, and may weaken the adhesion between the polymer layer and the third active layer and the second active layer; if n and m are greater than 10,000, the molecular weight of the third polymer will be high, the third polymer will easily agglomerate in the slurry, and the third polymer in the polymer layer will be unevenly distributed, which will affect the electrochemical performance of the battery and increase the difficulty of processing and preparation.

[0025] Since the ratio of n to m is 0.1-10, the number of structural units containing R1 and the number of structural units containing R2 are relatively close, and the length of the chain segment composed of the structural units containing R1 and the length of the chain segment composed of the structural units containing R2 are also relatively close. Therefore, not only the structural orderliness of the block copolymer can be improved, and its physical and chemical properties can be improved, but also the adhesion between the polymer layer and the second active layer and the adhesion with the third active layer can be made more balanced. Further, when the polymer layer is subjected to external force, the stress distribution inside it is more uniform, thereby improving the adhesion between the polymer layer and the second active layer and the third active layer.

[0026] In a possible implementation, the thickness of the polymer layer is 0.1 μm-5 μm. Thus, not only can the third active layer and the second active layer be bonded together well, thereby reducing the Hi-Pot test failure rate, but also the battery capacity and energy density are higher.

[0027] In a possible implementation, an opening of the groove faces a side of the third active layer away from the second active layer, a bottom of the groove is opposite to the opening, and the bottom of the groove is located in the third active layer or the second active layer.

[0028] By setting the groove 30 not to penetrate into the first active layer 21 , on the one hand, it can be avoided that the groove 30 is too deep so as to weaken the strength of the negative electrode plate 100 , and on the other hand, it can be avoided that the active material content of the negative electrode plate 100 is too low to affect the electrochemical performance.

[0029] In a possible implementation, the mass percentage of the silicon material in the second active layer is greater than 10% and less than or equal to 70%, which can enable the battery to have a higher battery capacity, energy density, first coulombic efficiency and a lower Hi-Pot test failure rate.

[0030] In a possible implementation, the mass percentage of the silicon material in the active layer 20 is greater than or equal to 5% and less than or equal to 50%, which can enable the battery to have a higher battery capacity, energy density, first coulombic efficiency and a lower Hi-Pot test failure rate.

[0031] In one possible implementation, the silicon material includes at least one of elemental silicon, silicon-carbon material and silicon-oxygen material. Elemental silicon has a high theoretical specific capacity, and introducing it into the second active layer can significantly improve the energy density of the battery. Silicon-carbon material combines the advantages of silicon and carbon, has a high specific capacity and good cycle stability, and also helps to improve the energy density of the battery. The volume change of silicon-oxygen material during the cycle is small, which is conducive to improving the cycle life of the battery.

[0032] In a possible implementation, the thickness of the first active layer is 5 μm-30 μm, the thickness of the second active layer is 20 μm-100 μm, the thickness of the third active layer is 5 μm-30 μm, and the depth of the groove is 5 μm-40 μm, so that the battery has a higher capacity and energy density.

[0033] In a possible implementation, a plurality of grooves are provided at intervals on a side of the third active layer away from the second active layer, the width of each groove is 40 μm-120 μm, and the distance between two adjacent grooves is 0.5 mm-3 mm. This can make the strength of the negative electrode plate higher, and the energy density of the battery including the negative electrode plate higher and the charge and discharge performance better.

[0034] In a possible implementation, an angle is formed between the length direction of the groove and the width direction of the third active layer, and the angle is 0°-10°, so that the filaments can be prevented from falling off during the slicing process.

[0035] In a possible implementation, the first active layer also includes a conductive agent and a binder, the mass percentage of the carbon material in the first active layer is 90%-95%, the mass percentage of the conductive agent is 1%-5%, and the mass percentage of the binder is 1%-5%; the second active layer also includes a carbon material, a conductive agent and a binder, the mass percentage of the carbon material in the second active layer is 20%-80%, the mass percentage of the conductive agent is 1%-5%, and the mass percentage of the binder is 1%-5%; the third active layer also includes a conductive agent and a binder, the mass percentage of the carbon material in the third active layer is 90%-98%, the mass percentage of the conductive agent is 1%-5%, and the mass percentage of the binder is 1%-5%.

[0036] Among them, the conductive agent can improve the conductivity of the active layer and improve the charge and discharge performance, and the binder can play a role in bonding the granular active materials together.

[0037] The second aspect of the present application provides a method for preparing a negative electrode sheet, and the preparation method is used to manufacture the negative electrode sheet as described in the first aspect. The preparation method comprises the steps of: providing a current collector, a first slurry, a second slurry, and a third slurry, wherein the first slurry and the third slurry both include carbon materials, and the second slurry includes silicon materials; coating the first slurry on the current collector to form a first active layer; coating the second slurry on the side of the first active layer away from the current collector to form a second active layer, and the mass percentage of the silicon material in the second active layer is greater than 10%; coating the third slurry on the side of the second active layer away from the first active layer to form a third active layer; and using a laser to open a groove on the side of the third active layer away from the second active layer.

[0038] In a possible implementation, the third slurry further includes a first precursor, wherein when a laser is used to open the groove on a side of the third active layer away from the second active layer, the first precursor is in-situ polymerized in the third active layer to form a first polymer.

[0039] In a possible implementation, the second slurry further includes a second precursor, wherein when a laser is used to open the groove on a side of the third active layer away from the second active layer, the second precursor is polymerized in situ in the second active layer to form a second polymer.

[0040] In a possible implementation, before coating the third slurry on the side of the second active layer away from the first active layer to form the third active layer, the method further includes: coating a polymer slurry on the side of the second active layer away from the first active layer to form a polymer layer, wherein the polymer slurry includes a third polymer. The aforementioned coating the third slurry on the side of the second active layer away from the first active layer to form the third active layer includes: coating the third slurry on the side of the polymer layer away from the second active layer to form the third active layer.

[0041] The preparation method provided in the second aspect is used to prepare the negative electrode plate provided in the first aspect, and thus can achieve the same or corresponding beneficial effects as the solution provided in the first aspect, and will not be described in detail here.

[0042] The third aspect of the present application provides a battery, comprising a positive electrode plate, a separator, and a negative electrode plate as described in the first aspect and its various implementations; wherein the separator is located between the positive electrode plate and the negative electrode plate.

[0043] The battery provided in the third aspect includes the negative electrode plate provided in the first aspect, and thus can achieve the same or corresponding beneficial effects as the solution provided in the first aspect, which will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the implementation manner will be briefly introduced below. Obviously, the drawings described below are some implementation manners of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0045] Figure 1 A schematic diagram of the cross-sectional structure of a negative electrode plate provided in some embodiments of the present application.

[0046] Figure 2 Schematic diagram of the cross-sectional structure of the negative electrode sheet provided in other embodiments of the present application.

[0047] Figure 3 Schematic diagram of the cross-sectional structure of the negative electrode plate provided in some further embodiments of the present application.

[0048] Figure 4 Schematic diagram of the cross-sectional structure of the negative electrode sheet provided in some other embodiments of the present application.

[0049] Figure 5 A schematic diagram of the planar structure of the negative electrode plate provided in some embodiments of the present application.

[0050] Figure 6 A flow chart of a method for preparing a negative electrode plate provided in some embodiments of the present application.

[0051] Figure 7 It is a schematic diagram of the cross-sectional structure obtained after executing step S4.

[0052] Figure 8 Schematic diagram of a battery in some embodiments of the present application.

[0053] Fig. 9 This is a structural block diagram of an electronic device in some embodiments of the present application. DETAILED DESCRIPTION

[0054] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0055] In the description of this application, the terms "first", "second", "third", etc. are used to distinguish different objects, rather than to describe a specific order, and therefore cannot be understood as limiting this application. The terms "upper", "bottom", etc. indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing this application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific position, be constructed and operate in a specific position, and therefore cannot be understood as limiting this application. In addition, "plurality" refers to two or more than two.

[0056] It should be noted that the illustrations provided in the embodiments of the present application are only used to illustrate the basic concept of the present application in a schematic manner. The illustrations only show the components related to the present application rather than being drawn according to the number, shape and size of the components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.

[0057] In the description of this application, words such as "exemplarily" or "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "exemplarily" or "for example" in this application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplarily" or "for example" is intended to present related concepts in a specific way.

[0058] Reference to "embodiments" in this application means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The presentation of the phrase at various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application may be combined with other embodiments.

[0059] In the lithium-ion battery in the related art, the morphology and structure of silicon will be destroyed during the continuous lithium insertion and extraction process, resulting in a low initial coulombic efficiency of the battery. In addition, the mass proportion of silicon-based negative electrode materials in the related art is relatively low, resulting in the application of silicon-based negative electrode materials in lithium-ion batteries being limited. In addition, in order to improve battery performance in the related art, grooves are made on the active layer. However, the applicant of this application has found through research that when grooves are made on the active layer containing silicon material, the escaped silicon dust will fall on the negative electrode sheet. After the negative electrode sheet, diaphragm, and positive electrode sheet are formed into a battery cell through winding or lamination processes, the battery cell needs to be pressurized so that the negative electrode sheet, diaphragm, and positive electrode sheet fit tightly. During the pressurization process, due to the high hardness and large particle size of silicon dust, the silicon dust may be squeezed and directly penetrate the diaphragm and connect the positive and negative electrode sheets, which may easily cause local short circuits under high voltage, resulting in a high Hi-Pot test failure rate, and thus a high battery cell failure rate.

[0060] The embodiment of the present application provides a negative electrode plate, which can improve the initial coulombic efficiency, battery capacity and energy density, and can also reduce the Hi-Pot test failure rate.

[0061] The battery involved in the embodiments of the present application is a secondary battery, for example, a lithium ion battery, a sodium ion battery, etc.

[0062] The negative electrode sheet provided in the embodiments of the present application is introduced below.

[0063] See also Figure 1 , is a schematic diagram of the cross-sectional structure of the negative electrode sheet 100 provided in some embodiments of the present application. Figure 1 As shown, the negative electrode plate 100 includes a current collector 10 and an active layer 20, wherein the active layer 20 is disposed on the current collector 10, and the active layer 20 includes a first active layer 21, a second active layer 22, and a third active layer 23 which are sequentially stacked on the current collector 10, wherein the first active layer 21 is closer to the current collector 10 than the second active layer 22, and a groove 30 is provided on a side of the third active layer 23 away from the second active layer 22. The first active layer 21 and the third active layer 23 include carbon materials, the second active layer 22 includes silicon materials, and the mass percentage of the silicon materials in the second active layer 22 is greater than 10%.

[0064] The negative electrode sheet 100 provided in the embodiment of the present application is provided with the first active layer 21, the second active layer 22 and the third active layer 23 stacked in sequence on the current collector 10. Since the first active layer 21 including carbon material is close to the current collector 10, the bonding force between the second active layer 22 and the first active layer 21 is greater than the bonding force between the second active layer 22 and the current collector 10, thereby preventing the second active layer 22 including silicon material from falling off from the current collector 10 due to expansion, thereby improving the first coulomb efficiency, energy density and battery capacity of the battery. In addition, since the mass percentage of silicon material in the second active layer 22 is greater than 10%, the active layer 20 has a higher silicon content, further improving the energy density and battery capacity. In addition, the groove 30 can increase the contact area between the active layer 20 and the electrolyte, thereby improving the infiltration effect of the electrolyte, and can also reduce the tortuosity, increase the battery charge and discharge rate, and improve the battery charge and discharge rate. Specifically, since the groove 30 can be used as a transmission path for ions such as lithium ions, lithium ions can reach the inside of the active layer 20 more directly and quickly, thereby reducing the tortuosity. In addition, compared with the related art of grooving on silicon materials, the embodiment of the present application can reduce the defective rate of the battery cell by grooving on the third active layer 23 including carbon materials. Specifically, since the carbon material has a lower hardness, smaller particle size, and lower density than the silicon material, the scattered carbon dust is not easy to fall on the negative electrode plate 100, and even if it falls on the negative electrode plate 100, when pressurized, the carbon dust with lower hardness and smaller particle size is not easy to penetrate the diaphragm, and thus it is not easy to produce a local short circuit, thereby reducing the Hi-Pot test defective rate and the battery cell defective rate.

[0065] The current collector 10 may be in the form of a plate or a sheet, and includes two opposite surfaces in the thickness direction of the current collector 10 , wherein the first active layer, the second active layer and the third active layer are sequentially stacked on the current collector, which means that the first active layer, the second active layer and the third active layer are sequentially stacked on one surface of the current collector 10 .

[0066] The active layer 20 may be disposed on one side of the current collector 10, or may be disposed on both surfaces of the current collector 10. When the active layer 20 is disposed on both surfaces of the current collector 10, the active layer 20 disposed on each surface may be the same, for example, including a first active layer 21, a second active layer 22, and a third active layer 23 sequentially stacked on the current collector 10, and a surface of the third active layer 23 away from the second active layer 22 is provided with a groove 30, and so on.

[0067] In some embodiments, the third active layer 23 further includes a first polymer, which is formed by in-situ polymerization of a first precursor in the third active layer 23 , and the first polymer is mixed with the carbon material and distributed in the third active layer 23 .

[0068] Among them, the first polymer is formed by in-situ polymerization of the first precursor, which means that the first polymer is added to the slurry in the form of the first precursor. After the slurry is coated to form the third active layer 23, when the third active layer 23 is grooved, the first precursor undergoes a polymerization reaction in the third active layer 23 to generate the first polymer, and the structure of the first polymer has a structural unit corresponding to the first precursor.

[0069] Among them, when the groove is opened, after the material of the third active layer 23 located in the groove area, especially the binder, escapes, the bonding strength between the material particles of the remaining material will be weakened, and the first precursor in the groove area is polymerized to generate the first polymer to form a cross-linked network, which can bond the material particles of the remaining material of the third active layer 23 in the groove area, thereby improving the bonding strength between the material particles of the third active layer 23 at the position of the groove 30, avoiding the material particles at this position from falling off, and then reducing the carbon material escape, and further reducing the Hi-Pot test failure rate, and avoiding the falling off of carbon material particles can improve the first coulomb efficiency and energy density. In addition, the first precursor located at other positions is polymerized to generate the first polymer, which can enhance the bonding strength between the material particles of the third active layer 23 at the corresponding position.

[0070] In some embodiments, the structure of the first precursor includes an aromatic ring and a double bond. The structure of the first precursor includes a double bond so that the first precursor can undergo a polymerization reaction. The structure of the first precursor includes an aromatic ring, that is, the first polymer generated by in-situ polymerization also includes an aromatic ring, so that the polarity of the first polymer is relatively weak. Due to the principle of similar compatibility, the first polymer with relatively weak polarity has good affinity with the non-polar carbon material in the third active layer 23, so that the first polymer and the carbon material in the third active layer 23 have good compatibility, and the first polymer and the carbon material have a large adhesion force, which can form a relatively stable structure.

[0071] In some embodiments, the first precursor includes at least one of allylbenzene, allylbenzyl ether, 2-allylphenyl allyl ether and 2-allylbenzaldehyde. The polymerization reaction of these precursors has high reaction efficiency, and the generated first polymer can better bond the materials of the third active layer 23 together. In addition, these precursors have high chemical stability and low cost.

[0072] In some other embodiments, the structure of the first precursor includes an ether oxygen bond and a double bond. For example, the first precursor includes at least one of polyethylene glycol diacrylate (PEGDA), polyethylene glycol methyl ether acrylate, and polyethylene glycol methyl ether methacrylate.

[0073] In some embodiments, the mass percentage of the first polymer in the third active layer 23 is 3%-5%. The mass percentage of the first polymer within this range can not only achieve a good bonding effect, and thus the Hi-Pot test failure rate is low, but also the first coulomb efficiency, battery capacity, and energy density are high. If the mass percentage of the first polymer is less than 3%, the bonding strength between the material particles of the third active layer 23 at the position of the groove 30 may be reduced, and the material particles may fall off, which may increase the Hi-Pot test failure rate and reduce the first coulomb efficiency, energy density, and battery capacity. If the mass percentage of the first polymer is greater than 5%, the mass proportion of the carbon material in the third active layer 23 will be reduced, thereby affecting the energy density and battery capacity.

[0074] In some embodiments, the second active layer 22 further includes a second polymer, which is formed by in-situ polymerization of a second precursor in the second active layer 22 , and the second polymer is mixed with the silicon material and distributed in the second active layer 22 .

[0075] Among them, the second polymer is formed by in-situ polymerization of the second precursor, which means that the second polymer is added to the slurry in the form of the second precursor. After the slurry is coated to form the second active layer 22, when a groove is opened on the third active layer 23 and penetrates into the second active layer 22, the second precursor undergoes a polymerization reaction in the second active layer 22 to generate the second polymer, and the structure of the second polymer has a structural unit corresponding to the second precursor.

[0076] Among them, when the grooves are opened, after the material of the second active layer 22 located in the grooved area, especially the binder, escapes, the bonding strength between the material particles of the remaining material will be weakened, and the second precursor in the grooved area is polymerized to generate the second polymer to form a cross-linked network, which can bond the material particles of the remaining material of the second active layer 22 in the grooved area, thereby improving the bonding strength between the material particles of the second active layer 22 at the position of the groove 30, thereby reducing the escape of silicon material, and further reducing the Hi-Pot test failure rate, and avoiding the shedding of silicon material particles can improve the first coulomb efficiency and energy density. In addition, the second precursor located at other positions is polymerized to generate the second polymer, which can enhance the bonding strength between the material particles of the second active layer 22 at the corresponding position. The second polymer can also inhibit the expansion of silicon material particles in the second active layer 22.

[0077] In some embodiments, the groove 30 provided on the side of the third active layer 23 away from the second active layer 22 at least penetrates the surface of the third active layer 23 away from the second active layer 22. The opening of the groove 30 faces the side of the third active layer 23 away from the second active layer 22, and the bottom of the groove 30 is located in the third active layer 23 or the second active layer 22, that is, the groove may penetrate part of the third active layer 23, or may penetrate the entire third active layer 23, or may further penetrate part or all of the second active layer 22. When the bottom of the groove 30 is located in the third active layer 23 or the second active layer 22, the second active layer 22 may include the second polymer.

[0078] In some embodiments, the structure of the second precursor includes an ether oxygen bond and a double bond. The structure of the second precursor includes a double bond, so that the second precursor can undergo a polymerization reaction. The structure of the second precursor includes an ether oxygen bond, which has a strong polarity and can produce a strong interaction with ions such as lithium ions, such as adsorption, coordination, etc., thereby facilitating the improvement of the ion transport performance of the second active layer 22, thereby improving the kinetic performance of the battery.

[0079] In some embodiments, the second precursor includes at least one of polyethylene glycol diacrylate, polyethylene glycol methyl ether acrylate, and polyethylene glycol methyl ether methacrylate. The polymerization reaction of these precursors is high in reaction efficiency, and the generated second polymer can better bond the materials of the second active layer 22 together. In addition, these precursors have high chemical stability and low cost.

[0080] Wherein, in some embodiments, the weight average molecular weight of the second precursor is 400-20000, which can make the polymerization efficiency of the second precursor higher, and the second precursor is not easy to agglomerate in the slurry. If the weight average molecular weight of the second precursor is less than 400, the second precursor is easy to volatilize and escape, and the required polymerization time is long, resulting in low polymerization efficiency. If the weight average molecular weight of the second precursor is greater than 20000, the second precursor is easy to agglomerate in the slurry, and it is difficult to form a uniform and continuous second precursor interface.

[0081] In some other embodiments, the second polymer in the second active layer 22 may include an aromatic ring and a double bond. For example, the second polymer may include at least one of allylbenzene, allylbenzyl ether, 2-allylphenyl allyl ether, and 2-allylbenzaldehyde.

[0082] In some embodiments, the mass percentage of the second polymer in the second active layer 22 is 3%-5%, which not only has a good bonding effect, and thus the Hi-Pot test failure rate is low, but also has high first coulomb efficiency, battery capacity, and energy density. If the mass percentage of the first polymer is less than 3%, the bonding strength between the material particles in the second active layer 22 may be reduced. For example, when the groove 30 penetrates into the second active layer 22, the bonding strength of the material particles of the second active layer 22 at the position of the groove 30 may be reduced, and the material particles may fall off, which may increase the Hi-Pot test failure rate and reduce the first coulomb efficiency, energy density, and battery capacity. If the mass percentage of the first polymer is greater than 5%, the mass proportion of the silicon material in the second active layer 22 will be reduced, thereby affecting the energy density and battery capacity.

[0083] See also Figure 2 , is a schematic diagram of the cross-sectional structure of the negative electrode sheet 100 provided in some other embodiments of the present application. Figure 2 As shown, in some embodiments, the negative electrode plate 100 includes not only the aforementioned current collector 10 and active layer 20, but also a polymer layer 40, and the polymer layer 40 is disposed between the third active layer 23 and the second active layer 22. The polymer layer 40 includes a third polymer, and the structure of the third polymer includes a first group and a second group, wherein the first group includes at least one of a carboxyl group (-COOH), a carboxylate (-COOM), an amide group (-CONH2), a hydroxyl group (-OH), a cyano group (-CN), and an ester group (-COOR), wherein M may be Na, K, etc., or other metal elements, R may be a non-hydrogen group, such as an alkyl group, etc., and the second group includes an aromatic group.

[0084] The first group in the third polymer has strong polarity, and forms hydrogen bonds or dipole-dipole interactions with the surface groups of the silicon material in the second active layer 22, which can enhance the adhesion between the polymer layer 40 and the second active layer 22. The second group in the third polymer is a non-polar group, and the second group can form a π...π interaction with the carbon material in the third active layer 23, which can enhance the adhesion between the polymer layer 40 and the third active layer 23. Thus, the polymer layer 40 can play a bonding role. The polymer layer 40 is arranged between the second active layer 22 and the third active layer 23, which can increase the bonding force between the second active layer 22 and the third active layer 23. When the third active layer 23 is grooved, the second active layer 22 and the third active layer 23 can be prevented from being partially separated under the action of external energy. For example, when the third active layer 23 is grooved using a laser, the second active layer 22 and the third active layer 23 can be prevented from being partially separated under the action of light and heat, thereby preventing the material particles of the third active layer 23 and the material particles of the second active layer 22 from falling off as much as possible, thereby further reducing the Hi-Pot test failure rate and improving the first coulomb efficiency.

[0085] In some embodiments, the third polymer has a structure shown in Formula I, Formula I, wherein R1 is the first group, R2 is the second group, R3 and R4 include at least one of carboxyl, hydroxyl, amino and hydrogen, wherein R3 and R4 may be the same or different.

[0086] In some embodiments, the first group is carboxyl, the second group is phenyl, and the third polymer is polyacrylic acid-styrene block copolymer. In other embodiments, the first group is -COOBu, the second group is phenyl, and the third polymer is polybutyl acrylate-styrene block copolymer.

[0087] In some embodiments, n and m are integers between 10 and 10,000. If n and m are less than 10, the molecular weight of the third polymer will be relatively low, which may cause the polymer layer 40 to have strong fluidity during processing and be difficult to form a stable coating, and may weaken the adhesion between the polymer layer 40 and the third active layer 23 and the second active layer 22. If n and m are greater than 10,000, the molecular weight of the third polymer will be relatively high, and the third polymer will easily agglomerate in the slurry, resulting in uneven distribution of the third polymer in the polymer layer 40, which will affect the electrochemical performance of the battery and increase the difficulty of processing and preparation.

[0088] In some embodiments, the ratio of n to m is 0.1-10, so that the number of structural units containing R1 and the number of structural units containing R2 are relatively close, and the length of the chain segment composed of the structural units containing R1 and the length of the chain segment composed of the structural units containing R2 are also relatively close. Therefore, not only can the structural order of the block copolymer be improved, thereby improving its physical and chemical properties, but also the adhesion between the polymer layer 40 and the second active layer 22 and the adhesion with the third active layer 23 can be made more balanced, and then when the polymer layer 40 is subjected to external force, the stress distribution inside it is more uniform, thereby improving the adhesion between the polymer layer 40 and the second active layer 22 and the third active layer 23.

[0089] In some embodiments, m may be greater than n. Since silicon material particles are prone to expansion during the charge and discharge process, by setting m greater than n, that is, the number of the first groups is greater than the number of the second groups, the volume change of the silicon material can be alleviated by utilizing the interaction between more of the first groups and the silicon material in the second active layer 22.

[0090] In some embodiments, the molecular weight of the third polymer is 5000-1000000. If the molecular weight of the third polymer is less than 5000, the polymer chain segment is short, it is not easy to form a stable coating, and the adhesion between the polymer layer 40 and the third active layer 23 and the second active layer 22 may be weakened; if the molecular weight of the third polymer is greater than 1000000, the third polymer may be easily agglomerated in the slurry, and the third polymer in the polymer layer 40 is unevenly distributed, and the difficulty of processing and preparation is increased.

[0091] In some embodiments, the thickness of the polymer layer 40 is 0.1 μm-5 μm, which can not only better bond the third active layer 23 and the second active layer 22 together, thereby reducing the Hi-Pot test failure rate, but also has higher battery capacity and energy density. If the thickness of the polymer layer 40 is less than 0.1 μm, the bonding strength between the third active layer 23 and the second active layer 22 is weak, which may increase the Hi-Pot test failure rate. If the thickness of the polymer layer 40 is greater than 5 μm, the mass proportion of the active material in the negative electrode plate 100 will be reduced, and the transmission performance of ions such as lithium ions may be affected, thereby affecting the battery capacity and energy density. Among them, the thickness of the polymer layer 40 is the size of the polymer layer 40 in the stacking direction of the active layer 20 and the current collector 10.

[0092] See also Figures 1 to 4 , Figure 3Schematic diagram of the cross-sectional structure of the negative electrode sheet 100 provided in some embodiments of the present application, Figure 4 Schematic diagram of the cross-sectional structure of the negative electrode sheet 100 provided in some embodiments of the present application. Figures 1 to 4 As shown, the opening 31 of the groove 30 faces the side of the third active layer 23 away from the second active layer 22 , and the bottom 32 of the groove 30 is opposite to the opening 31 .

[0093] In some embodiments, Figure 1 and Figure 2 As shown, the bottom 32 of the groove 30 is located in the third active layer 23 , that is, the groove 30 extends into the third active layer 23 , wherein the groove 30 may penetrate the third active layer 23 along the stacking direction of the active layer 20 and the current collector 10 , or may not penetrate the third active layer 23 .

[0094] When the negative electrode plate 100 includes the polymer layer 40 , the bottom 32 of the groove 30 may be located in the polymer layer 40 , that is, the groove 30 extends deep into the polymer layer 40 , wherein the groove 30 may penetrate the polymer layer 40 along the stacking direction of the active layer 20 and the current collector 10 , or may not penetrate the polymer layer 40 .

[0095] In other embodiments, Figure 3 and Figure 4 As shown, the bottom 32 of the groove 30 is located in the second active layer 22 , that is, the groove 30 extends into the second active layer 22 , wherein the groove 30 may penetrate the second active layer 22 along the stacking direction of the active layer 20 and the current collector 10 , or may not penetrate the second active layer 22 .

[0096] By setting the groove 30 not to penetrate into the first active layer 21 , on the one hand, it can be avoided that the groove 30 is too deep so as to weaken the strength of the negative electrode plate 100 , and on the other hand, it can be avoided that the active material content of the negative electrode plate 100 is too low to affect the electrochemical performance.

[0097] Preferably, in some embodiments, the bottom 32 of the groove 30 is located in the second active layer 22 and does not penetrate the second active layer 22. By setting the groove 30 to penetrate into the second active layer 22, the contact area between the second active layer 22 and the electrolyte can be increased, the electrolyte infiltration effect of the second active layer 22 can be improved, and the tortuosity of the second active layer 22 can be reduced, which helps ions such as lithium ions to reach the inside of the second active layer 22 more directly and quickly, thereby facilitating the improvement of the transmission efficiency of lithium ions in the second active layer 22.

[0098] In some embodiments, the mass percentage of the silicon material in the second active layer 22 is greater than 10% and less than or equal to 70%, which can enable the battery to have a higher battery capacity, energy density, first coulomb efficiency and a lower Hi-Pot test failure rate. If the mass percentage of the silicon material is less than 10%, the battery capacity and energy density will be reduced; if the mass percentage of the silicon material is greater than 70%, due to the high content of the silicon material, the silicon material particles may expand and rupture, thereby causing the first coulomb efficiency to decrease, and if the groove is deep into the second active layer 22, the high content of the silicon material may cause the Hi-Pot test failure rate to increase.

[0099] Preferably, in some embodiments, the mass percentage of the silicon material in the second active layer 22 is greater than 10% and less than or equal to 40%, which can reduce the defect rate of the Hi-Pot test of the battery.

[0100] In some embodiments, the mass percentage of the silicon material in the active layer 20 is greater than or equal to 5% and less than or equal to 50%, which can make the battery have a higher battery capacity, energy density, first coulomb efficiency and lower Hi-Pot test failure rate. If the mass percentage of the silicon material in the active layer 20 is less than 5%, the silicon content of the negative electrode plate 100 is low, then the contribution of the silicon material to the capacity is limited, limiting the improvement of the battery energy density. If the mass percentage of the silicon material in the active layer 20 is greater than 50%, the volume expansion of the silicon material during the charge and discharge process may destroy the structure of the active layer 20, resulting in a decrease in the first coulomb efficiency and battery capacity, and an increase in the Hi-Pot test failure rate.

[0101] In some embodiments, the mass percentage of the silicon material in the active layer 20 is greater than or equal to 10% and less than or equal to 40%, which can enable the battery to have a higher battery capacity and better cycle performance.

[0102] In some embodiments, the silicon material in the second active layer 22 includes at least one of elemental silicon, silicon-carbon material and silicon-oxygen material. Elemental silicon has a high theoretical specific capacity, and introducing it into the second active layer can significantly improve the energy density of the battery. Silicon-carbon material combines the advantages of silicon and carbon, has a high specific capacity and good cycle stability, and also helps to improve the energy density of the battery. The volume change of silicon-oxygen material during the cycle is small, which is conducive to improving the cycle life of the battery.

[0103] In some other embodiments, the silicon material is other types of silicon materials.

[0104] In some embodiments, the carbon material in the first active layer 21 and the third active layer 23 includes at least one of graphite, hard carbon and soft carbon. The types of the carbon materials in the first active layer 21 and the third active layer 23 may be the same or different. In some other embodiments, the carbon material is other types of carbon materials.

[0105] In some embodiments, the thickness of the first active layer 21 is 5 μm-30 μm, the thickness of the second active layer 22 is 20 μm-100 μm, the thickness of the third active layer 23 is 5 μm-30 μm, and the depth of the groove 30 is 5 μm-40 μm. The thickness of the first active layer 21, the thickness of the second active layer 22, the thickness of the third active layer 23, and the depth of the groove 30 are all dimensions along the stacking direction of the active layer 20 and the current collector 10.

[0106] If the thickness of the first active layer 21, the second active layer 22 and the third active layer 23 is lower than the lower limit of the corresponding thickness range, the battery capacity may be low. If the thickness of the first active layer 21, the second active layer 22 and the third active layer 23 is higher than the upper limit of the corresponding thickness range, since the negative electrode sheet 100 is thicker, the effective utilization area of ​​the active material is reduced, which may lead to a decrease in capacity and energy density, and the diffusion distance of ions in the electrode is increased, which may increase the resistance during the charge and discharge process and reduce the charge and discharge efficiency. In addition, the thicker negative electrode sheet 100 is more likely to change in volume during the charge and discharge process, causing powdering and falling off, shortening the cycle life.

[0107] If the depth of the groove 30 is less than 5 μm, the effect on improving the electrolyte infiltration effect and reducing the tortuosity is limited. If the depth of the groove 30 is greater than 40 μm, the groove 30 is too deep, which may cause the strength of the negative electrode plate 100 to be weak and the active material of the active layer 20 to be lost, thereby affecting the battery capacity.

[0108] In some embodiments, a plurality of grooves 30 are provided on one side of the third active layer 23 away from the second active layer 22, each groove 30 has a width of 40 μm-120 μm, and the spacing between two adjacent grooves 30 is 0.5 mm-3 mm, which can not only significantly improve the infiltration effect of the electrolyte and reduce the tortuosity, but also enable the negative electrode plate 100 to have a higher structural strength. The widths of the plurality of grooves 30 may be the same or different, and the spacing between two adjacent grooves 30 may be the same or different. The width of the groove 30 is the dimension in a direction perpendicular to the length direction of the groove 30.

[0109] If the width of the groove 30 is less than 40 μm, the effect of improving electrolyte wetting and reducing tortuosity may be limited due to the small width of the groove 30. If the width of the groove 30 is greater than 120 μm, the strength of the negative electrode sheet 100 may be reduced due to the large width of the groove 30.

[0110] If the distance between two adjacent grooves 30 is less than 0.5 mm, that is, the distance between two adjacent grooves 30 is small, the plurality of grooves 30 are densely distributed, which may reduce the strength of the negative electrode plate 100. If the distance between two adjacent grooves 30 is greater than 3 mm, that is, the distance between two adjacent grooves 30 is large, the plurality of grooves 30 are sparsely distributed, which may have limited effect on improving the electrolyte infiltration effect and reducing the tortuosity.

[0111] In some embodiments, there is an angle between the length direction of the groove 30 and the width direction of the third active layer 23, and the angle is greater than or equal to 0° and less than or equal to 10°. The width direction of the third active layer 23 is perpendicular to the extension direction of the third active layer 23, that is, the length direction.

[0112] For example, see Figure 5 , is a schematic diagram of the planar structure of the negative electrode sheet 100 provided in some embodiments of the present application. Figure 5 As shown, the angle between the length direction of the groove 30 and the width direction of the negative electrode plate 100 , that is, the width direction (Y direction) of the third active layer 23 is 0°.

[0113] In order to meet the requirements of battery design, the negative electrode sheet 100 is usually cut along the width direction of the negative electrode sheet 100 to obtain slices with sizes that meet the requirements. When the angle is 0°, that is, the length direction of the groove 30 is parallel to the width direction of the negative electrode sheet 100, since the cutting direction is parallel to the width direction of the negative electrode sheet 100, by setting the cutting position of the blade between two adjacent grooves 30, the blade will not cut into the groove 30, thereby preventing the material wire from falling.

[0114] In some cases, due to the deviation of the cutting position in the actual cutting process, after multiple cuts, the cutting position of the blade may get closer and closer to the groove 30. When the deviation is superimposed until the blade just cuts the groove 30, the blade will cut the groove 30 along the length direction of the groove 30, and then the material wire will fall off. By setting the angle greater than 0°, that is, the groove 30 is tilted relative to the third active layer 23, even if the cutting position has a deviation, the blade cuts the groove 30, and the blade will not cut the groove 30 along the length direction of the groove 30, thereby minimizing the falling of the material wire. Furthermore, by setting the angle less than or equal to 10°, that is, the groove 30 is slightly tilted relative to the third active layer 23, the length of multiple grooves 30 in the slices obtained after cutting can be relatively small, that is, the length of multiple grooves 30 is relatively uniform, which is conducive to improving the electrolyte infiltration effect and the balance of ion transmission performance.

[0115] In some other embodiments, the angle may be greater than 10°, such as 20°, 45°, 90°, etc.

[0116] In some embodiments, the shape of the groove 30 may be as follows: Figure 5 The straight line shown may be a curved line, or may be any other shape as required.

[0117] In some embodiments, the third active layer 23 also includes a conductive agent and a binder, the mass percentage of the carbon material in the third active layer 23 is 90%-95%, the mass percentage of the conductive agent in the third active layer 23 is 1%-5%, and the mass percentage of the binder in the third active layer 23 is 1%-5%.

[0118] The conductive agent in the third active layer 23 can improve the conductivity of the third active layer 23, reduce the resistance of the third active layer 23, and accelerate the movement rate of electrons, thereby improving the charge and discharge performance of the battery. The first polymer generated by the in-situ polymerization of the first precursor and the binder can both play a role in connecting the granular carbon material and the conductive agent together to ensure the structural integrity and stability of the third active layer 23.

[0119] In some embodiments, the second active layer 22 further includes a carbon material, a conductive agent and a binder, the mass percentage of the carbon material in the second active layer 22 is 20%-80%, the mass percentage of the conductive agent in the second active layer 22 is 1%-5%, and the mass percentage of the binder in the second active layer 22 is 1%-5%.

[0120] Among them, the conductive agent in the second active layer 22 can improve the conductivity of the second active layer 22, reduce the resistance of the second active layer 22, accelerate the movement rate of electrons, and thus improve the charge and discharge performance of the battery. The second polymer generated by the in-situ polymerization of the second precursor and the binder can both play the role of connecting the granular silicon material, carbon material, and conductive agent together to ensure the structural integrity and stability of the second active layer 22. By adding carbon material and silicon material in the second active layer 22, the expansion of the silicon material can be alleviated to a certain extent, and the cycle stability of the battery can be improved.

[0121] In some embodiments, the first active layer 21 further includes a conductive agent and a binder, the mass percentage of the carbon material in the first active layer 21 is 90%-98%, the mass percentage of the conductive agent in the first active layer 21 is 1%-5%, and the mass percentage of the binder in the first active layer 21 is 1%-5%.

[0122] The conductive agent in the first active layer 21 can improve the conductivity of the first active layer 21, reduce the resistance of the first active layer 21, and accelerate the movement rate of electrons, thereby improving the charge and discharge performance of the battery. The binder in the first active layer 21 can connect the granular carbon material and the conductive agent together to ensure the structural integrity and stability of the first active layer 21.

[0123] The following describes a method for preparing a negative electrode sheet provided in an embodiment of the present application.

[0124] See also Figure 6 , is a flow chart of a method for preparing a negative electrode sheet provided in some embodiments of the present application. The preparation method is used to manufacture the negative electrode sheet 100 described in any of the aforementioned embodiments. Figure 6 As shown, the preparation method comprises the following steps: S1: providing a current collector 10, a first slurry, a second slurry, and a third slurry, wherein the first slurry and the third slurry both include carbon materials, and the second slurry includes silicon materials.

[0125] S2 : coating the first slurry on the current collector 10 to form a first active layer 21 .

[0126] S3: coating the second slurry on a side of the first active layer 21 away from the current collector 10 to form a second active layer 22 , wherein the mass percentage of the silicon material in the second active layer 22 is greater than 10%.

[0127] S4: Coating the third slurry on the side of the second active layer 22 away from the first active layer 21 to form a third active layer 23. The structure after forming the third active layer 23 is as follows: Figure 7 shown.

[0128] S5: Using laser to open a groove 30 on the side of the third active layer 23 away from the second active layer 22. The structure after opening the groove is as follows: Figure 1 shown.

[0129] When laser grooving is used, a laser beam can be used to irradiate the side of the third active layer 23 away from the second active layer 22. The material in the third active layer 23 absorbs the laser energy and converts it into heat energy, so that the material in the irradiated area melts, decomposes, and evaporates, thereby achieving the removal of the material in the irradiated area. Alternatively, the material in the second active layer 22 melts, decomposes, and evaporates due to heat to form the groove 30.

[0130] The depth of the groove 30 can be controlled by controlling the energy of the laser beam, the irradiation time, etc., so as to control the bottom 32 of the groove 30 to be located in the third active layer 23 or the second active layer 22 .

[0131] In some embodiments, during laser grooving, the power of the laser device is 100W-2000W, and the laser beam quality M 2 The factor is less than 1.5, so that the emitted laser can not only etch away a portion of the third active layer 23, or further etch away a portion of the second active layer 22 to form the groove 30, but also the energy of the laser is sufficient to induce the first precursor in the third active layer 23 to undergo an in-situ polymerization reaction to generate the first polymer, or further induce the second precursor in the second active layer 22 to undergo an in-situ polymerization reaction to generate the second polymer.

[0132] In some embodiments, the first slurry may further include the aforementioned conductive agent, the aforementioned binder, and a solvent. The second slurry may further include a carbon material, the aforementioned conductive agent, the aforementioned binder, and a solvent. The third slurry may further include the aforementioned conductive agent, the aforementioned binder, and a solvent. The solvent may be deionized water or an organic solvent.

[0133] In some embodiments, the third slurry further includes a first precursor and a first initiator, and the first precursor, the first initiator and the carbon material are uniformly mixed in the third slurry. When performing step S5, that is, when the groove 30 is opened on the side of the third active layer 23 away from the second active layer 22 using a laser, the first initiator triggers the first precursor to undergo a polymerization reaction under the action of the laser, so that the first precursor is polymerized in situ in the third active layer 23 to form the aforementioned first polymer.

[0134] In some embodiments, the first initiator may include a photoinitiator. When the laser irradiates the third active layer 23, the photoinitiator in the third active layer 23 absorbs the laser energy and undergoes a decomposition reaction to generate free radicals. The generated free radicals combine with the first precursor molecules to generate first precursor free radicals. The generated first precursor free radicals combine with other first precursor molecules to form a polymer chain, thereby generating the first polymer.

[0135] Wherein, the photoinitiator may include at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and ethyl 2,4,6-trimethylbenzoylphenylphosphonate. The first precursor may include at least one of the aforementioned allylbenzene, allyl benzyl ether, 2-allylphenyl allyl ether and 2-allylbenzaldehyde. The first precursor may undergo a polymerization reaction under the action of the photoinitiator.

[0136] In other embodiments, the first initiator may include a thermal initiator. When the laser irradiates the third active layer 23, the material in the third active layer 23 absorbs the laser energy and converts it into thermal energy, causing the temperature to rise. Then, the thermal initiator in the third active layer 23 decomposes under the heat to generate free radicals. The generated free radicals combine with the first precursor molecules to generate first precursor free radicals. The generated first precursor free radicals combine with other first precursor molecules to form polymer chains, thereby generating the first polymer.

[0137] Wherein, the thermal initiator may include at least one of azobisisoheptanonitrile, azobismethoxyisoheptanonitrile, dilauroyl peroxide, dicyclohexyl peroxydicarbonate, benzoyl peroxide, azobisisobutyronitrile, and potassium persulfate. The first precursor may include at least one of the aforementioned polyethylene glycol diacrylate, polyethylene glycol methyl ether acrylate, and polyethylene glycol methyl ether methacrylate. The first precursor may undergo a polymerization reaction under the action of the thermal initiator.

[0138] Wherein, the first initiator may be at least one of the above-mentioned photoinitiator and thermal initiator.

[0139] In some embodiments, the second slurry further includes a second precursor and a second initiator, and the second precursor, the second initiator and the silicon material are uniformly mixed in the second slurry. When performing step S5, that is, using a laser to open the groove 30 on the side of the third active layer 23 away from the second active layer 22, the second initiator will induce the second precursor to undergo a polymerization reaction, so that the second precursor is polymerized in situ in the second active layer 22 to form the aforementioned second polymer.

[0140] In some embodiments, the second initiator may include a thermal initiator. When the laser irradiates the third active layer 23, the third active layer 23 absorbs the laser energy and converts it into thermal energy. The converted thermal energy is transmitted to the second active layer 22. In addition, the second active layer 22 may also absorb the laser energy and convert it into thermal energy. The thermal energy increases the temperature of the second active layer 22, and then the thermal initiator in the second active layer 22 decomposes under the heat to generate free radicals. The generated free radicals combine with the second precursor molecules to generate second precursor free radicals. The generated second precursor free radicals combine with other second precursor molecules to form polymer chains, thereby generating the second polymer.

[0141] Wherein, the thermal initiator may include at least one of azobisisoheptanonitrile, azobismethoxyisoheptanonitrile, dilauroyl peroxide, dicyclohexyl peroxydicarbonate, benzoyl peroxide, azobisisobutyronitrile, and potassium persulfate. The first precursor may include at least one of the aforementioned polyethylene glycol diacrylate, polyethylene glycol methyl ether acrylate, and polyethylene glycol methyl ether methacrylate. The second precursor may undergo a polymerization reaction under the action of the thermal initiator.

[0142] In other embodiments, the second initiator may include a photoinitiator. When irradiated by laser, the photoinitiator in the second active layer 22 absorbs laser energy and undergoes a decomposition reaction to generate free radicals. The generated free radicals combine with second precursor molecules to generate second precursor free radicals. The generated second precursor free radicals combine with other second precursor molecules to form polymer chains, thereby generating the second polymer.

[0143] Wherein, the photoinitiator may include at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and ethyl 2,4,6-trimethylbenzoylphenylphosphonate. The first precursor may include at least one of the aforementioned allylbenzene, allyl benzyl ether, 2-allylphenyl allyl ether and 2-allylbenzaldehyde. The second precursor may undergo a polymerization reaction under the action of the photoinitiator.

[0144] Wherein, the second initiator may be at least one of the above-mentioned photoinitiator and thermal initiator.

[0145] Preferably, in some embodiments, the first initiator in the third active layer 23 may be a photoinitiator, and the second initiator in the second active layer 22 may be a thermal initiator, and the decomposition temperature of the thermal initiator is lower than 70°C, and the half-life is 7h-13h, for example, 10h. Wherein, the first initiator may include at least one of 2-hydroxy-2-methyl-1-phenylacetone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and the second initiator may include at least one of azobisisoheptanenitrile, azobismethoxyisoheptanenitrile, dilauroyl peroxide and dicyclohexyl peroxydicarbonate.

[0146] That is, the polymerization system in the third active layer 23 is a photo-initiated polymerization system, and the polymerization system in the second active layer 22 is a thermally initiated polymerization system. Since the laser is directly irradiated on the third active layer 23, the first initiator can directly absorb the laser energy and initiate polymerization, thereby improving the polymerization efficiency. Since the second active layer 22 is located on the side of the third active layer 23 away from the laser, by setting the second initiator as a thermal initiator, and having a low decomposition temperature and a short half-life, when the second active layer 22 receives the heat energy conducted by the third active layer 23, the second initiator can quickly decompose at a low temperature to generate free radicals, thereby initiating polymerization, thereby improving the polymerization efficiency.

[0147] When the first initiator is a photoinitiator, the mass ratio of the photoinitiator to the first precursor is 0.1:100 to 5:100. When the second initiator is a photoinitiator, the mass ratio of the photoinitiator to the second precursor is 0.1:100 to 5:100. Thus, the photoinitiator can generate sufficient free radicals to initiate the polymerization reaction of the precursor and reduce the generation of by-products.

[0148] When the first initiator is a thermal initiator, the mass ratio of the thermal initiator to the first precursor is 1:100 to 10:100. When the second initiator is a thermal initiator, the mass ratio of the thermal initiator to the second precursor is 1:100 to 10:100. Thus, the thermal initiator can generate sufficient free radicals to initiate the polymerization reaction of the precursor and reduce the generation of by-products.

[0149] In some embodiments, the solid content of the first slurry may be 30%-56%, for example, 43%. The solid content of the second slurry may be 35%-65%, for example, 50%. The solid content of the third slurry may be 34%-63%, for example, 48%. Thus, the slurry can be evenly coated.

[0150] In some embodiments, before step S4 of "coating the third slurry on the side of the second active layer 22 away from the first active layer 21 to form the third active layer 23", the method for preparing the negative electrode sheet further includes the step of: coating a polymer slurry on the side of the second active layer 22 away from the first active layer 21 to form a polymer layer 40, wherein the polymer slurry includes a third polymer and a solvent, and the solid content of the polymer slurry may be 7%-13%, for example, 10%. The solvent may be deionized water or an organic solvent.

[0151] Step S4 “coating the third slurry on the side of the second active layer 22 away from the first active layer 21 to form the third active layer 23 ” includes: coating the third slurry on the side of the polymer layer 40 away from the second active layer 22 to form the third active layer 23 .

[0152] See also Figure 8 , is a schematic diagram of a battery 200 in some embodiments of the present application. Figure 8 As shown, an embodiment of the present application further provides a battery 200 , wherein the battery 200 includes a positive electrode plate 210 , a separator 220 , and the negative electrode plate 100 described in any of the aforementioned embodiments, wherein the separator 220 is located between the positive electrode plate 210 and the negative electrode plate 100 .

[0153] See also Fig. 9 , is a structural block diagram of an electronic device 300 in some embodiments of the present application. Fig. 9 As shown, the embodiment of the present application further provides an electronic device 300 , and the electronic device 300 includes the battery 200 .

[0154] Among them, the electronic device can be a mobile phone, a tablet computer, a laptop computer, a large-screen device (for example: smart TV, smart screen), a computer, a wearable electronic device, a vehicle-mounted device, a virtual reality device, an electric car, a home appliance, a drone, etc.

[0155] The electronic device may further include other components, such as a display screen, a memory, etc., which are irrelevant to the improvement of the present invention and are not described in detail here.

[0156] The present application is described in detail below with reference to Implementation Examples 1-23 and Comparative Examples 1-2. The following implementation examples are only used to illustrate and explain the present application, and the protection scope of the present application is not limited by the following implementation examples.

[0157] Implementation Example 1 (1) Preparation of the first slurry: Graphite, conductive agent and binder in a mass ratio of 92:4:4 were mixed with deionized water to obtain a first slurry with a solid content of 43%. Preparation of the second slurry: Deposited silicon carbon, graphite, conductive agent, binder, polyvinyl alcohol diacrylate and dilauroyl peroxide in a mass ratio of 40:54:2:1:3:0.03 were mixed with deionized water to obtain a second slurry with a solid content of 50%, wherein the weight average molecular weight of polyvinyl alcohol diacrylate was 20,000. Preparation of the third slurry: Graphite, conductive agent, binder, allyl benzyl ether and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of 94:2:1:3:0.03 were mixed with deionized water to obtain a third slurry with a solid content of 48%. Preparation of polymer slurry: Polyacrylic acid-styrene block copolymer was mixed with deionized water to obtain a polymer slurry with a solid content of 10%.

[0158] (2) Slurry coating: a first slurry, a second slurry, a polymer slurry and a third slurry are sequentially coated on opposite sides of the copper foil and dried to obtain a first active layer 21, a second active layer 22, a polymer layer 40 and a third active layer 23, wherein the thickness of the first active layer 21 is 10 μm, the thickness of the second active layer 22 is 40 μm, the thickness of the polymer layer 40 is 1 μm, and the thickness of the third active layer 23 is 10 μm.

[0159] (3) Laser grooving: A laser is used to etch the side of the third active layer 23 away from the copper foil to form a plurality of grooves 30. The depth of the grooves 30 is 20 μm, the width of the grooves is 60 μm, and the distance between two adjacent grooves 30 is 1 mm, thereby obtaining the negative electrode sheet 100. The power of the laser device is 500 W, and the beam quality is M 2 The factor is less than 1.5. The mass percentage of deposited silicon carbon in the second active layer 22 of the negative electrode plate 100 is 40%, the mass percentage of deposited silicon carbon in the active layer 20 is 30%, the mass percentage of the first polymer in the third active layer 23 is 3%, and the mass percentage of the second polymer in the second active layer 22 is 3%.

[0160] (4) Battery assembly: The negative electrode sheet 100 obtained after laser grooving is stacked with the separator and the positive electrode sheet to obtain a battery cell, and the battery cell is made into a soft-pack battery.

[0161] Implementation Example 2 Implementation Example 2 is different from Implementation Example 1 in that the mass ratio of deposited silicon carbon, graphite, conductive agent, binder, polyvinyl alcohol diacrylate and dilauroyl peroxide in the second slurry is 7.4:54:2:1:3:0.03, the mass percentage of deposited silicon carbon in the second active layer 22 of the negative electrode plate 100 is 11%, and the mass percentage of deposited silicon carbon in the active layer 20 is 5%.

[0162] Implementation Example 3 Implementation Example 3 is different from Implementation Example 1 in that the mass ratio of deposited silicon carbon, graphite, conductive agent, binder, polyvinyl alcohol diacrylate and dilauroyl peroxide in the second slurry is 140:54:2:1:3:0.03, the mass percentage of deposited silicon carbon in the second active layer 22 of the negative electrode plate 100 is 70%, and the mass percentage of deposited silicon carbon in the active layer 20 is 50%.

[0163] Implementation Example 4 Implementation Example 4 is different from Implementation Example 1 in that the mass ratio of deposited silicon carbon, graphite, conductive agent, binder, polyvinyl alcohol diacrylate and dilauroyl peroxide in the second slurry is 5:54:2:1:3:0.03, the mass percentage of deposited silicon carbon in the second active layer 22 of the negative electrode plate 100 is 8%, and the mass percentage of deposited silicon carbon in the active layer 20 is 4%.

[0164] Implementation Example 5 Implementation Example 5 is different from Implementation Example 1 in that the mass ratio of deposited silicon carbon, graphite, conductive agent, binder, polyvinyl alcohol diacrylate and dilauroyl peroxide in the second slurry is 180:54:2:1:3:0.03, the mass percentage of deposited silicon carbon in the second active layer 22 of the negative electrode plate 100 is 75%, and the mass percentage of deposited silicon carbon in the active layer 20 is 52%.

[0165] Implementation Example 6 Implementation Example 6 is different from Implementation Example 1 in that the mass ratio of graphite, conductive agent, binder, allyl benzyl ether and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in the third slurry is 94:2:1:5:0.03, and the mass percentage of the first polymer in the third active layer 23 of the negative electrode plate 100 is 5%.

[0166] Implementation Example 7 Implementation Example 7 is different from Implementation Example 1 in that the mass ratio of graphite, conductive agent, binder, allyl benzyl ether and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in the third slurry is 94:2:1:2:0.03, and the mass percentage of the first polymer in the third active layer 23 of the negative electrode plate 100 is 2%.

[0167] Implementation Example 8 Implementation Example 8 is different from Implementation Example 1 in that the mass ratio of graphite, conductive agent, binder, allyl benzyl ether and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in the third slurry is 94:2:1:6:0.03, and the mass percentage of the first polymer in the third active layer 23 of the negative electrode plate 100 is 6%.

[0168] Implementation Example 9 Implementation Example 9 is different from Implementation Example 1 in that the mass ratio of silicon carbon, graphite, conductive agent, binder, polyvinyl alcohol diacrylate and dilauroyl peroxide deposited in the second slurry is 40:54:2:1:5:0.03, and the mass percentage of the second polymer in the second active layer 22 of the negative electrode plate 100 is 5%.

[0169] Implementation Example 10 Implementation Example 10 is different from Implementation Example 1 in that the mass ratio of silicon carbon, graphite, conductive agent, binder, polyvinyl alcohol diacrylate and dilauroyl peroxide deposited in the second slurry is 40:54:2:1:2:0.03, and the mass percentage of the second polymer in the second active layer 22 of the negative electrode plate 100 is 2%.

[0170] Implementation Example 11 Implementation Example 11 is different from Implementation Example 1 in that the mass ratio of silicon carbon, graphite, conductive agent, binder, polyvinyl alcohol diacrylate and dilauroyl peroxide deposited in the second slurry is 40:54:2:1:6:0.03, and the mass percentage of the second polymer in the second active layer 22 of the negative electrode plate 100 is 6%.

[0171] Implementation Example 12 Implementation Example 12 is different from Implementation Example 1 in that: the first precursor and the first initiator are not added to the third slurry, that is, there is no first polymer in the third active layer 23 ; the second precursor and the second initiator are not added to the second slurry, that is, there is no second polymer in the second active layer 22 .

[0172] Implementation Example 13 The difference between Embodiment 13 and Embodiment 1 is that the thickness of the polymer layer 40 is 0.1 μm.

[0173] Implementation Example 14 The difference between Embodiment 14 and Embodiment 1 is that the thickness of the polymer layer 40 is 5 μm.

[0174] Implementation Example 15 The difference between Embodiment 15 and Embodiment 1 is that the thickness of the polymer layer 40 is 0.05 μm.

[0175] Implementation Example 16 The difference between Embodiment 16 and Embodiment 1 is that the thickness of the polymer layer 40 is 6 μm.

[0176] Implementation Example 17 Compared with Embodiment 1, Embodiment 17 is different in that no polymer slurry is coated, that is, no polymer layer 40 is included in the negative electrode sheet 100 .

[0177] Implementation Example 18 (1) Preparation of the first slurry: Graphite, a conductive agent, and a binder in a mass ratio of 92:4:4 were mixed evenly with deionized water to obtain a first slurry with a solid content of 43%. Preparation of the second slurry: Deposited silicon carbon, graphite, a conductive agent, and a binder in a mass ratio of 40:57:2:1 were mixed evenly with deionized water to obtain a second slurry with a solid content of 50%. Preparation of the third slurry: Graphite, a conductive agent, a binder, polyvinyl alcohol diacrylate, and potassium persulfate in a mass ratio of 94:2:1:3:0.03 were mixed evenly with deionized water to obtain a third slurry with a solid content of 48%, wherein the weight average molecular weight of polyvinyl alcohol diacrylate was 20,000.

[0178] (2) Slurry coating: a first slurry, a second slurry, and a third slurry are sequentially coated on opposite sides of the copper foil and dried to obtain a first active layer 21, a second active layer 22, and a third active layer 23. The thickness of the first active layer 21 is 10 μm, the thickness of the second active layer 22 is 40 μm, and the thickness of the third active layer 23 is 10 μm.

[0179] (3) Laser grooving: A laser is used to etch the side of the third active layer 23 away from the copper foil to form a plurality of grooves 30. The depth of the grooves 30 is 20 μm, the width of the grooves is 60 μm, and the distance between two adjacent grooves 30 is 1 mm, thereby obtaining the negative electrode sheet 100. The power of the laser device is 500 W, and the beam quality is M 2 The factor is less than 1.5. The mass percentage of deposited silicon carbon in the second active layer 22 of the negative electrode plate 100 is 40%, the mass percentage of deposited silicon carbon in the active layer 20 is 30%, and the mass percentage of the first polymer in the third active layer 23 is 3%.

[0180] (4) Battery assembly: The negative electrode sheet 100 obtained after laser grooving is stacked with the separator and the positive electrode sheet to obtain a battery cell, and the battery cell is made into a soft-pack battery.

[0181] Implementation Example 19 The difference between Embodiment 19 and Embodiment 18 is that the depth of the groove 30 is 10 μm.

[0182] Implementation Example 20 The difference between the embodiment 20 and the embodiment 18 is that the depth of the groove 30 is 30 μm.

[0183] Implementation Example 21 The difference between the embodiment 21 and the embodiment 18 is that the thickness of the first active layer 21 is 5 μm, and the thickness of the second active layer 22 is 45 μm.

[0184] Implementation Example 22 Compared with the embodiment 18, the embodiment 22 is different in that the thickness of the second active layer 22 is 45 μm, and the thickness of the third active layer 23 is 5 μm.

[0185] Implementation Example 23 The difference between Implementation Example 23 and Implementation Example 18 is that polyvinyl alcohol diacrylate and potassium persulfate are not added to the first slurry, and the third active layer 23 does not contain the first polymer.

[0186] Comparative Example 1 (1) Slurry preparation: Graphite, conductive agent and binder in a mass ratio of 92:4:4 were mixed with deionized water to obtain a slurry with a solid content of 43%.

[0187] (2) Slurry coating: The slurry is sequentially coated on opposite sides of the copper foil and dried to obtain a negative electrode sheet, wherein the negative electrode sheet has an active layer with a thickness of 60 μm.

[0188] (3) Battery assembly: The negative electrode sheet, the separator and the positive electrode sheet are stacked to obtain a battery cell, and the battery cell is made into a soft-pack battery.

[0189] Comparative Example 2 (1) Slurry preparation: Graphite, deposited silicon carbon, conductive agent and binder in a mass ratio of 62:30:4:4 were mixed with deionized water to obtain a slurry with a solid content of 43%.

[0190] (2) Slurry coating: Slurry is sequentially coated on opposite sides of the copper foil and dried to obtain an active layer, wherein the thickness of the active layer is 60 μm.

[0191] (3) Laser grooving: A laser is used to etch the side of the active layer away from the copper foil to form a number of grooves with a depth of 20 μm, a width of 60 μm, and a spacing of 1 mm between two adjacent grooves to obtain the negative electrode. The power of the laser equipment is 500 W and the beam quality is M 2 The factor is less than 1.5.

[0192] (4) Battery assembly: The negative electrode sheet obtained after laser grooving is stacked with the separator and the positive electrode sheet to obtain a battery cell, and the battery cell is made into a soft-pack battery.

[0193] The thickness of the first active layer 21, the second active layer 22, the third active layer 23, and the polymer layer 40 in the above-mentioned embodiments 1-23, and the thickness of the active layer in the above-mentioned comparative examples 1-2, can all be measured by a spiral micrometer, or by a SEM (Scanning Electron Microscope). The depth of the groove 30, the width of the groove 30, and the spacing of the grooves 30 in the above-mentioned embodiments 1-23, and the depth of the grooves, the width of the grooves, and the spacing of the grooves in the above-mentioned comparative example 2 can all be measured by SEM.

[0194] The relevant parameters of Implementation Examples 1-23 can be found in Table 1, and the relevant parameters of Comparative Examples 1-2 can be found in Table 2.

[0195] Table 1

[0196] Table 1

[0197] Table 1

[0198] Among them, in Table 1, A represents allyl benzyl ether and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, B represents PEGDA and K2O8S2, C represents polyacrylic acid-styrene block copolymer, and D represents PEGDA and dilauroyl peroxide.

[0199] Table 2

[0200] The cells prepared in Example 1-23 and Comparative Example 1-2 were subjected to a Hi-Pot test, and the test conditions were: voltage 100 V, test time 2±1 s, pressure 0.16±0.02 MPa, and the passing standard was internal resistance ≥4 MΩ.

[0201] The soft-pack batteries assembled in Example 1-23 and Comparative Example 1-2 were subjected to a 0.2C discharge capacity test to obtain the 0.2C discharge capacity, and the first coulombic efficiency and energy density were obtained. The conditions for the 0.2C discharge capacity test were as follows: the soft-pack battery was charged to 4.55V at a constant current of 0.2C, then charged at a constant voltage until the current was less than 0.02C or the charging time was greater than or equal to 180 minutes, and then discharged to 2.75V at a constant current of 0.2C.

[0202] Among them, during the calculation of energy density, the thickness of the soft-pack battery is measured by a PPG (Panel Pressure Gap) thickness gauge.

[0203] The test results of the above Hi-Pot test, the 0.2C discharge capacity, the first coulombic efficiency and the energy density obtained by the test are shown in Table 3.

[0204] Table 3

[0205] It can be seen from the energy densities corresponding to Implementation Examples 1-23 and Comparative Example 1 in Table 3 that the negative electrode plate 100 includes silicon material, which can significantly improve the energy density of the battery.

[0206] It can be seen from the 0.2C discharge capacity, first coulomb efficiency, energy density and Hi-Pot defective rate corresponding to Example 23 and Comparative Example 2 in Table 3 that, compared with directly grooving the active layer comprising silicon material, the third active layer 23 comprising carbon material is provided on the second active layer 22 comprising silicon material, and grooving is performed on the third active layer 23, which can significantly reduce the Hi-Pot defective rate. Among them, compared with carbon material, silicon material has a larger hardness, larger particle size and irregular morphology, which can easily cause local micro-short circuits, thereby easily causing Hi-Pot test failure. In this application, the third active layer 23 comprising carbon material is grooved, which can significantly reduce the Hi-Pot defective rate. In addition, the present application also provides the first active layer 21 between the second active layer 22 and the current collector 10. The multi-layer active layer structure of the negative electrode sheet 100 of the present application improves the 0.2C discharge capacity, first coulomb efficiency and energy density of the battery.

[0207] From the 0.2C discharge capacity and energy density corresponding to Implementation Examples 1-4 in Table 3, it can be seen that the discharge capacity and energy density when the silicon material content in the second active layer 22 is greater than 10% are higher than the discharge capacity and energy density when the silicon material content is less than 10%. From the first coulomb efficiency and Hi-Pot defect rate corresponding to Implementation Examples 1-3 and 5 in Table 3, it can be seen that the first coulomb efficiency and Hi-Pot defect rate when the silicon material content in the second active layer 22 is less than or equal to 70% are respectively higher and lower than the first coulomb efficiency when the silicon material content is greater than 70%. Among them, increasing the silicon material content can increase the discharge capacity and energy density, but too high a silicon material content can easily lead to poor Hi-Pot test and affect the machinability of the negative electrode sheet 100. In order to balance energy density and machinability, it is necessary to select a suitable silicon material content. Therefore, considering the 0.2C discharge capacity, first coulomb efficiency, energy density and Hi-Pot defect rate, selecting the silicon material content in the second active layer 22 greater than 10% and less than or equal to 70% for battery production can make the battery performance better. Furthermore, it can be seen from the test results of implementation examples 1-3 that the Hi-Pot defective rate is 0 when the silicon material content in the second active layer 22 is greater than 10% and less than or equal to 40%, and the Hi-Pot defective rate is 6.95% when the silicon material content is greater than 40% and less than or equal to 70%, indicating that the Hi-Pot test performance is better when the silicon material content is greater than 10% and less than or equal to 40%. Therefore, it is further preferred that the silicon material content in the second active layer 22 is greater than 10% and less than or equal to 40%.

[0208] From the 0.2C discharge capacity, first coulomb efficiency, energy density and Hi-Pot defective rate corresponding to Implementation Examples 1, 6-7 in Table 3, it can be seen that the 0.2C discharge capacity, first coulomb efficiency and energy density when the mass percentage of the first polymer in the third active layer 23 is 3%-5% are higher than the corresponding values ​​when the mass percentage of the first polymer is 2%, and the Hi-Pot defective rate is lower than the Hi-Pot defective rate when the mass percentage of the first polymer is 2%. From the 0.2C discharge capacity, first coulomb efficiency and energy density corresponding to Implementation Examples 1, 6 and 8 in Table 3, it can be seen that the 0.2C discharge capacity, first coulomb efficiency and energy density when the mass percentage of the first polymer in the third active layer 23 is 3%-5% are higher than the corresponding values ​​when the mass percentage of the first polymer is 6%. Among them, if the content of the first polymer is too low, it may affect the binding of the dust generated by the laser grooving, increase the Hi-Pot defective rate, and then affect the processing performance; if the content of the first polymer is too high, it may hinder carrier transmission, which is not conducive to rate performance and reduces battery capacity and energy density. Therefore, considering the 0.2C discharge capacity, the first coulombic efficiency, the energy density and the Hi-Pot defect rate, the battery performance is better when the mass percentage of the first polymer in the third active layer 23 is within the range of 3%-5%.

[0209] From the first coulombic efficiency, energy density and Hi-Pot defective rate corresponding to implementation examples 1, 9-10 in Table 3, it can be seen that the first coulombic efficiency and energy density when the mass percentage of the second polymer in the second active layer 22 is 3%-5% are higher than the corresponding values ​​when the mass percentage of the second polymer is 2%, and the Hi-Pot defective rate is lower than the Hi-Pot defective rate when the mass percentage of the second polymer is 2%. From the first coulombic efficiency and energy density corresponding to implementation examples 1, 9, and 11 in Table 3, it can be seen that the first coulombic efficiency and energy density when the mass percentage of the second polymer in the second active layer 22 is 3%-5% are higher than the corresponding values ​​when the mass percentage of the second polymer is 6%. Among them, if the content of the second polymer is too low, it will affect the binding of dust generated by laser grooving, increase the Hi-Pot defective rate, and then affect the processing performance; if the content of the second polymer is too high, it will hinder carrier transmission, which is not conducive to rate performance and reduces battery capacity and energy density. Therefore, considering the first coulombic efficiency, energy density and Hi-Pot failure rate, the battery performance is better when the mass percentage of the second polymer in the second active layer 22 is within the range of 3%-5%.

[0210] It can be seen from the first coulombic efficiency, energy density and Hi-Pot defective rate corresponding to Implementation Examples 1 and 12 in Table 3 that if the third active layer 23 does not include the first polymer and the second active layer 22 does not include the second polymer, the first coulombic efficiency is significantly reduced, the Hi-Pot defective rate is significantly improved, and the energy density is also reduced, indicating that setting the third active layer 23 to include the first polymer and the second active layer 22 to include the second polymer can significantly improve the battery performance.

[0211] From the first coulombic efficiency and Hi-Pot defective rate corresponding to implementation examples 1, 13-15, and 17 in Table 3, it can be seen that the first coulombic efficiency and Hi-Pot defective rate when the thickness of the polymer layer 40 is 0.1μm-5μm are higher and lower than the corresponding values ​​of the thickness of 0.05μm, respectively. From the first coulombic efficiency and energy density corresponding to implementation examples 1, 13-14, and 16 in Table 3, it can be seen that the first coulombic efficiency and energy density when the thickness of the polymer layer 40 is 0.1μm-5μm are higher than the corresponding values ​​of the thickness of 6μm. Among them, if the thickness of the polymer layer 40 is too low, it will affect the adhesion of the third active layer 23 and the second active layer 22, and increase the Hi-Pot defective rate; if the thickness of the polymer layer 40 is too high, it will hinder carrier transmission, which is not conducive to rate performance and reduces battery capacity and energy density. Therefore, considering the first coulombic efficiency, energy density and Hi-Pot defect rate, the battery performance is better when the thickness of the polymer layer 40 is 0.1 μm-5 μm.

[0212] It can be seen from the first coulombic efficiency, energy density and Hi-Pot defective rate corresponding to implementation examples 18-19 in Table 3 that when the thickness of the third active layer 23 is 10 μm and the depth of the groove 30 is 20 μm, that is, when the groove 30 penetrates into the second active layer 22, the first coulombic efficiency and energy density are higher than the corresponding values ​​when the depth of the groove 30 is 10 μm, and the Hi-Pot defective rate is lower, indicating that the battery performance is better when the groove 30 penetrates into the second active layer 22. Among them, the groove 30 penetrates into the second active layer 22, which is conducive to the contact between the electrolyte and the second active layer 22, and reduces the tortuosity of the second active layer 22, thereby helping ions such as lithium ions to reach the interior of the second active layer 22 more directly and quickly, and then helps to improve the transmission efficiency of lithium ions in the second active layer 22, thereby helping to improve the energy density and the first coulombic efficiency. It can be seen from the first coulombic efficiency, energy density and Hi-Pot defect rate corresponding to Implementation Examples 18 and 20 in Table 3 that the depth of the groove 30 is greater than 20 μm, which will increase the Hi-Pot defect rate.

[0213] It can be seen from the 0.2C discharge capacity, first coulombic efficiency, energy density and Hi-Pot defective rate corresponding to Implementation Examples 18 and 21 in Table 3 that reducing the thickness of the third active layer 23 and increasing the thickness of the second active layer 22 will reduce the battery capacity, first coulombic efficiency, energy density and increase the Hi-Pot defective rate.

[0214] It can be seen from the 0.2C discharge capacity, first coulombic efficiency, energy density and Hi-Pot defective rate corresponding to Implementation Examples 18 and 22 in Table 3 that, compared with Implementation Example 18, reducing the thickness of the first active layer 21 and increasing the thickness of the second active layer 22 will reduce the battery capacity, first coulombic efficiency, energy density and increase the Hi-Pot defective rate.

[0215] The above is an implementation method of the embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the embodiment of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate comprises: current collector; An active layer is arranged on the current collector, the active layer includes a first active layer, a second active layer and a third active layer which are sequentially stacked on the current collector, the first active layer is closer to the current collector than the second active layer, and a groove is provided on a side of the third active layer away from the second active layer, wherein the first active layer and the third active layer include carbon material, the second active layer includes silicon material, and the mass percentage of the silicon material in the second active layer is greater than 10%.

2. The negative electrode sheet according to claim 1, characterized in that: The third active layer further includes a first polymer, which is formed by in-situ polymerization of a first precursor in the first active layer, and the first polymer is mixed with the carbon material and distributed in the third active layer.

3. The negative electrode sheet according to claim 2, characterized in that: The structure of the first precursor includes an aromatic ring and a double bond.

4. The negative electrode sheet according to claim 3, characterized in that: The first precursor includes at least one of allylbenzene, allylbenzyl ether, 2-allylphenyl allyl ether and 2-allylbenzaldehyde.

5. The negative electrode sheet according to claim 2, characterized in that: The mass percentage of the first polymer in the third active layer is 3%-5%.

6. The negative electrode sheet according to claim 1, characterized in that: The second active layer further includes a second polymer, which is formed by in-situ polymerization of a second precursor in the second active layer, and the second polymer is mixed with the silicon material and distributed in the second active layer.

7. The negative electrode sheet according to claim 6, characterized in that: The structure of the second precursor includes an ether oxygen bond and a double bond.

8. The negative electrode sheet according to claim 7, characterized in that: The second precursor includes at least one of polyethylene glycol diacrylate, polyethylene glycol methyl ether acrylate and polyethylene glycol methyl ether methacrylate.

9. The negative electrode sheet according to claim 6, characterized in that: The weight average molecular weight of the second precursor is 400-20000.

10. The negative electrode sheet according to claim 6, characterized in that: The mass percentage of the second polymer in the second active layer is 3%-5%.

11. The negative electrode sheet according to claim 1, characterized in that: The negative electrode plate also includes a polymer layer, which is arranged between the third active layer and the second active layer. The polymer layer includes a third polymer. The structure of the third polymer includes a first group and a second group. The first group includes at least one of a carboxyl group, a carboxylate group, an amide group, a hydroxyl group, a cyano group and an ester group, and the second group includes an aromatic group.

12. The negative electrode sheet according to claim 11, characterized in that: The third polymer has a structure shown in Formula I, Formula I, wherein R1 is the first group, R2 is the second group, R3 and R4 include at least one of carboxyl, hydroxyl, amino and hydrogen, n and m are integers between 10 and 10000, and the ratio of n to m is 0.1 to 10.

13. The negative electrode sheet according to claim 11, characterized in that: The thickness of the polymer layer is 0.1 μm-5 μm.

14. The negative electrode sheet according to claim 1, characterized in that: The opening of the groove faces the side of the third active layer away from the second active layer, the bottom of the groove is opposite to the opening, and the bottom of the groove is located in the third active layer or the second active layer.

15. The negative electrode sheet according to claim 1, characterized in that: The mass percentage of the silicon material in the second active layer is greater than 10% and less than or equal to 70%.

16. The negative electrode sheet according to claim 1, characterized in that: The mass percentage of the silicon material in the active layer is greater than or equal to 5% and less than or equal to 50%.

17. The negative electrode plate according to claim 1, characterized in that: The silicon material includes at least one of elemental silicon, silicon-carbon material and silicon-oxygen material.

18. The negative electrode sheet according to claim 1, characterized in that: The thickness of the first active layer is 5 μm-30 μm, the thickness of the second active layer is 20 μm-100 μm, the thickness of the third active layer is 5 μm-30 μm, and the depth of the groove is 5 μm-40 μm.

19. The negative electrode sheet according to claim 1, characterized in that: A plurality of grooves are arranged at intervals on a side of the third active layer away from the second active layer, the width of each groove is 40 μm-120 μm, and the distance between two adjacent grooves is 0.5 mm-3 mm.

20. The negative electrode plate according to claim 1, characterized in that: An angle is formed between the length direction of the groove and the width direction of the third active layer, and the angle is 0°-10°.

21. The negative electrode sheet according to claim 1, characterized in that: The first active layer also includes a conductive agent and a binder, the mass percentage of the carbon material in the first active layer is 90%-95%, the mass percentage of the conductive agent is 1%-5%, and the mass percentage of the binder is 1%-5%; the second active layer also includes a carbon material, a conductive agent and a binder, the mass percentage of the carbon material in the second active layer is 20%-80%, the mass percentage of the conductive agent is 1%-5%, and the mass percentage of the binder is 1%-5%; the third active layer also includes a conductive agent and a binder, the mass percentage of the carbon material in the third active layer is 90%-98%, the mass percentage of the conductive agent is 1%-5%, and the mass percentage of the binder is 1%-5%.

22. A method for preparing a negative electrode sheet, characterized in that: The preparation method is used to manufacture the negative electrode sheet according to any one of claims 1 to 21, and the preparation method comprises: Providing a current collector, a first slurry, a second slurry, and a third slurry, wherein the first slurry and the third slurry both include carbon materials, and the second slurry includes silicon materials; coating the first slurry on the current collector to form a first active layer; The second slurry is coated on a side of the first active layer away from the current collector to form a second active layer, wherein the mass percentage of the silicon material in the second active layer is greater than 10%; Coating the third slurry on a side of the second active layer away from the first active layer to form a third active layer; A groove is formed on a side of the third active layer away from the second active layer by using a laser.

23. The method for preparing a negative electrode sheet according to claim 22, characterized in that: The third slurry further includes a first precursor, wherein when a laser is used to open the groove on a side of the third active layer away from the second active layer, the first precursor is in-situ polymerized in the third active layer to form a first polymer.

24. The method for preparing a negative electrode sheet according to claim 22, characterized in that: The second slurry further includes a second precursor, wherein when a laser is used to open the groove on a side of the third active layer away from the second active layer, the second precursor is in-situ polymerized in the second active layer to form a second polymer.

25. The method for preparing a negative electrode sheet according to claim 22, characterized in that: Before coating the third slurry on a side of the second active layer away from the first active layer to form a third active layer, the method further includes: coating a polymer slurry on a side of the second active layer away from the first active layer to form a polymer layer, wherein the polymer slurry includes a third polymer; The step of coating the third slurry on a side of the second active layer away from the first active layer to form a third active layer comprises: The third slurry is coated on a side of the polymer layer away from the second active layer to form the third active layer.

26. A battery, characterized in that: The battery comprises a positive electrode sheet, a separator and a negative electrode sheet as claimed in any one of claims 1 to 21; wherein the separator is located between the positive electrode sheet and the negative electrode sheet.

Citation Information

Patent Citations

  • Biocampatible rechargable energization elements for biomedical devices

    CN105390708A

  • Stack for an energy storage device

    CN112437995A

  • Silicon negative electrode plate and preparation method and application thereof

    CN116864692A

  • Negative pole piece, preparation method thereof, lithium ion battery and electric vehicle

    CN118281161A

  • Negative plate and lithium ion secondary battery

    CN118630134A

Cited By

  • Battery pole piece, preparation method thereof and battery

    CN120072839A

  • Battery electrode sheet and preparation method therefor, and battery

    WO2026188990A1